1996
DOI: 10.2166/wst.1996.0209
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of domestic sewage from rural settlements by a membrane bioreactor

Abstract: This study examined the feasibility of applying a membrane bioreactor to small wastewater treatment using a pilot-scale plant. The operation was continued for 336 days. From the start to 251st day, the operation was continued without membrane washing. During the latter term of the operation, however, suction pressure increased rapidly corresponding to the increase of sludge viscosity. Because sludge viscosity increase occurred right after the suspension of sludge wasting, excess sludge must be wasted at regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Two types of MBR have been used according to the location of the membrane unit, i.e., membranes are submerged in the reactor or positioned external to the reactor. The submerged membrane type has attracted great attention in recent years since it is more compact and energy saving (144)(145)(146). It has the drawback that control of membrane fouling is more difficult to achieve than external membrane systems.…”
Section: Results Of Recent Investigations On Anaerobic Treatment Of Mmentioning
confidence: 99%
“…Two types of MBR have been used according to the location of the membrane unit, i.e., membranes are submerged in the reactor or positioned external to the reactor. The submerged membrane type has attracted great attention in recent years since it is more compact and energy saving (144)(145)(146). It has the drawback that control of membrane fouling is more difficult to achieve than external membrane systems.…”
Section: Results Of Recent Investigations On Anaerobic Treatment Of Mmentioning
confidence: 99%
“…Many approaches are reported concerning how to calculate these properties depending on the TSS (Krauth, 1993;Lübbecke, 1995;Ohle, 1999;Shimizu, 1996;Ueda, 1996;Xing, 2001). Because of the temperatures and concentrations considered in this work, the correlations of Ohle (Ohle, 1999) and Krauth (Krauth, 1993) were chosen.…”
Section: Properties Of the Bulk Phasementioning
confidence: 99%
“…The mini cleans may be backwash or simply intermittent permeation. This intermittent suction appears to be an effective technique for long-term sustainability of moderate fluxes [17], [18]. Various research and papers on membrane fouling in MBR technology has been reported showing the effect that different parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%